Introduction to ILWIS GIS tool - Montesinos S.; Fernández L. (The use of remote sensing and geographic information systems for irrigation management in Southwest Europe, 2012)
ILWIS for Windows is a Windows-based, integrated GIS and Remote Sensing application consisting of: (i) Display of raster and multiple vector maps in map windows; (ii) Display of tables in table windows; (iii) Interactive retrieval of attribute information, (iv) Image processing facilities, (v) Manipulation of maps in a Map Calculator; (vi) Manipulation of tables in a Table Calculator; (vii) GIS analysis tools and (viii) Script language to perform 'batch' jobs. With Windows, you can start one operation and keep it running while you start one or more additional applications. This is a sort of multitasking. You may work with both Windows and DOS application programs, you can perform one or more ILWIS calculations in the background and at the same time display maps, run other ILWIS operations, print, etc. http://52north.org/communities/ilwis/.